Budaya Digital dalam Adopsi Akuntansi Berbasis Cloud: Pendekatan Netnografi - Ismail, Juniaty; Olilingo, Fahrudin Zain; Hinelo, Raflin; Amaliah, Tri Handayani (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) STIE Tri Dharma Nusantara, 2025)
This study aims to explore the role of digital culture in the adoption of cloud-based accounting in Indonesia. A qualitative approach with a netnographic method was employed to understand how public narratives emerging from user reviews, online forums, and product descriptions shape legitimacy, trust, and resistance toward digital accounting applications. Data were collected from public platforms such as G2, Google Play Store, official application websites, and relevant review blogs, focusing on three Indonesian cloud-based accounting applications: Mekari Jurnal, Accurate Online, and Kledo. Thematic analysis was applied to identify key patterns and emerging themes within digital interactions. The findings reveal five main themes: automation and efficiency, reporting and customization, customer support and performance, security and privacy, and collective learning and community. Positive and negative narratives formed within digital spaces significantly influence the strengthening or weakening of application legitimacy. The results indicate that the adoption of cloud accounting is not only driven by technical and organizational factors as described in the TAM and TOE models but also by social legitimacy emerging from digital culture. The study implies the importance of digital reputation management for vendors and the role of regulators in enhancing digital literacy and public trust.